Preliminary study on the characteristics of FO/PRO hollow fiber membranes - Chen, Yunfeng. (2013)
With rapid development of industrialization and fast expansion in global population, there is an increasing need for sustainable energy and clean water resources. Energy crisis has become a global issue and limited access to clean water is now a great challenge for many people around the world. Osmotic process has become an attractive solution for these problems as it develops very fast in a broad variety of applications including desalination (using Forward Osmosis (FO)) and energy generation (using Pressure Retarded Osmosis (PRO)) though FO/PRO still faces many challenges. This report will firstly review the development and challenges of FO/PRO membranes and then describe the basic steps of fabrication, modifications and evaluation of PRO membranes. The main purpose of the project is to develop a thin-film composite (TFC) hollow fiber (HF) membrane that is suitable for PRO operation and conduct a series of characterization on the newly developed membrane. Polyetherimide (PEI) is selected to fabricate the membrane substrate as it has higher tensile modulus than polyether sulfone (PES), which is a common used material in current hollow fiber membrane fabrication. Interfacial polymerization technique is applied to make the selective layer on the membrane substrate.